Your second life begins when you realize you only have one - Giordano, Raphaëlle, 1974- (G.P. Putnam's Sons, 2018)
"The feel-good #1 bestselling French novel about a woman whose mission to cure her "routine-itis" leads her to lasting joy and true fulfillment, for fans of The Alchemist and Hector and the Search for Happiness. At thirty-eight and a quarter years old, Paris native Camille has everything she needs to be happy, or so it seems: a good job, a loving husband, a wonderful son. Why then does she feel as if happiness has slipped through her fingers? All she wants is to find the path to joy. When Claude, a French Sean Connery look-alike and routinologist, offers his unique advice to help get her there, she seizes the opportunity with both hands. Camille's journey is full of surprising escapades, creative capers, and deep meaning, as she sets out to transform her life and realize her dreams one step at a time. A charming, feel-good, and universal story of one woman's journey from boredom and dissatisfaction to happiness and fulfilment."--